Scott, Chaucer, and Medieval Romance : A Study in Sir Walter Scott's Indebtedness to the Literature of the Middle Ages - Mitchell, Jerome (Book collections on Project MUSE., 1987)
While the influence of Shakespeare on Sir Walter Scott has long been recognized, the importance of medieval literature in shaping his creative imagination has never before been examined in depth. Jerome Mitchell's new book fills this significant gap through a wide-ranging study of Scott's indebtedness to Chaucer and to medieval romance, especially the Middle English romances, for story-patterns, motifs, character types, style and structure, and detail. Mitchell establishes more completely and accurately than any previous critic the extent of Scott's knowledge of medieval literature. His examina.